Галузеві особливості договірного регулювання ризиків у соціально-трудових відносинах - Олійник, О.О. (Економіка промисловості, 2012)
Проаналізовано реальний стан використання генеральної та галузевих угод у регулюванні ризиків у соціально-трудових відносинах. Виявлено основні проблеми угод різних рівнів та шляхи їх вирішення. Ключові слова: генеральна угода, галузева угода, соціально-трудові відносини, ризик. Проанализировано реальное состояние использования генеральной и отраслевых соглашений в регулировании рисков в социальнотрудовых отношениях. Выявлены основные проблемы соглашений разных уровней и пути их решения Ключевые слова: генеральное соглашение, отраслевое соглашение, социально-трудовые отношения, риски. The paper analyzes the structure of general and branch agreements. The features of contractual regulation of risks in social and labour relations in some industries of the economy are described. The real situation in the use of general and branch agreements on regulation of risks in social and labour relations is analyzed. The basic problems concerning the application of agreements on different levels are revealed and the ways of their solution as well. Keywords: general agreement, branch agreement, social and labour relations, risk.